Commodity-industry classificationproxy: A correspondence table between SITC revision 2 and ISIC revision 3 - Mohammad Affendy, Arip; Lau, Sim Yee; Satoru, Madono (Munich University Library, 2010)
The correspondence table is one of the important tools in categorizing existing records into different perspective. It helps to understand the pattern of various economic activities from single source of data. Nevertheless, most of the existing correspondence tables have been focusing more on the latest classification and neglect the correspondence for the older version. Since some analysis would require longer series of data, therefore it is necessary to create a correspondence table for the earlier version of classification. This paper devoted to create a correspondence table between SITC Revision 2 and ISIC Revision 3 using a proxy method. The proxy is done using the SITC Rev.2 – SITC Rev.3 correspondence table and the SITC Rev.3 – ISIC Rev.3 correspondence table. This method has capable to directly find an industrial match for more than 98 percent of commodities under SITC Rev.3. For remaining commodities which industrial category cannot be matched directly, the identification was done automatically based on the closest code.